Aspects of Legal Protection for Franchisees Associated with the Franchise Agreement - Prasetyo, Stephanie Patricia; Urbaniasi, Urbaniasi (CV. Rayyan Dwi Bharata, 2023)
Franchising as a business concept regarding the granting of the use of intellectual property rights by the franchisor to the franchisee is a legal relationship between the franchisor and the franchisee which is regulated in a franchise agreement. The purpose of this article is to analyze aspects of legal protection for franchisees related to franchise agreements and to analyze legal sanctions against franchisors who break the agreement unilaterally. The research method is in the form of normative law whose implementation is focused on secondary data collection (Library Materials) covering primary legal materials such as laws and regulations, primary legal materials such as articles, books and so on. This research is descriptive in nature. By using a qualitative approach/paradigm. The data is processed and analyzed qualitatively using deductive logic. The franchisor is the licenser to the franchisee to market goods and services on behalf of the franchisor in a certain area and period of time. The franchisor assists the franchisee in its distribution, in return the franchisee pays an initial fee and royalties. The franchisor can determine the contents of the agreement and terminate the agreement unilaterally with the franchisee for the agreement that has been agreed upon, but termination of this franchise agreement can result in default, because it causes losses to the franchisee and it is the franchisor's obligation to pay compensation. Legal protection for the parties in the implementation of the franchise agreement is an important aspect. The form of legal protection for franchisees in franchise agreements is contained in Government Regulation Number 42 of 2007 concerning Franchising in the provisions of Article 5 letter (k) which stipulates that the franchise agreement establishes procedures for extending, terminating and terminating the agreement. Thus the franchisor cannot terminate the agreement unilaterally at any time, the franchisor must comply with the PP on Franchising and in accordance with the Civil Code.